Development of CO2 Selective Poly(Ethylene Oxide)-Based Membranes: From Laboratory to Pilot Plant Scale. (August 2017) - Brinkmann, Torsten; Lillepärg, Jelena; Notzke, Heiko; Pohlmann, Jan; Shishatskiy, Sergey; Wind, Jan; Wolff, Thorsten
Abstract: Membrane gas separation is one of the most promising technologies for the separation of carbon dioxide (CO2 ) from various gas streams. One application of this technology is the treatment of flue gases from combustion processes for the purpose of carbon capture and storage. For this application, poly(ethylene oxide)-containing block copolymers such as Pebax ® or PolyActive™ polymer are well suited. The thin-film composite membrane that is considered in this overview employs PolyActive™ polymer as a selective layer material. The membrane shows excellent CO2 permeances of up to 4 m 3 (STP)·(m 2 ·h·bar) −1 (1 bar = 10 5  Pa) at a carbon dioxide/nitrogen (CO2 /N2 ) selectivity exceeding 55 at ambient temperature. The membrane can be manufactured reproducibly on a pilot scale and mounted into flat-sheet membrane modules of different designs. The operating performance of these modules can be accurately predicted by specifically developed simulation tools, which employ single-gas permeation data as the only experimental input. The performance of membranes and modules was investigated in different pilot plant studies, in which flue gas and biogas were used as the feed gas streams. The investigated processes showed a stable separation performance, indicating the applicability of PolyActive™ polymer as a membrane material for industrial-scale gas processing.